THE OBJECTIVE SIDE OF THE CRIME OF ENDANGERMENT - Jumaevich, Khaydarov Shukhratjon (International Journal of Business, Law and Political Science, 2024)
This article describes in detail the risks associated with the criminal prosecution of Tomoni and uninga uziga. In this regard, in connection with violations related to the use of the lens, in connection with violations related to the use of the lens, in connection with violations related to the use of the lens, in connection with violations related to the use of the lens, in connection with violations, related to the use of the lens, in connection with violations related to the use of the lens, in connection with violations related to the use of the lens, in connection with violations related to the use of the lens, in connection with violations related to the use of the lens. In this verse, Allah swt said: While in other cases it may lead to a violation of law and order, in other cases it may lead to a violation of law and order